A study on digital inclusion of Chinese rural older adults from a life course perspective - Zhang, Huan; He, Ruimin (Frontiers in Public Health, 2022)
Digital inclusion is viewed as a crucial strategy for promoting social inclusion and addressing issues related to aging. This study focuses on the digital inclusion practices of rural senior citizens and introduces a life course research perspective to move the study of influencing factors from the proximal to the distal end. The motivations, trajectories, and barriers to digital inclusion among rural elderly groups are presented through participant observation and semi-structured interviews with 34 elderly people in a village in northern China. It was discovered that digital inclusion or exclusion is the cumulative result of life events, social roles, and personal agency in the life course, while it is difficult for the elderly to break away from traditional culture and social relations in rural areas in the digital age. The digital practice is not only an inner adjustment in the process of life stage transition for rural seniors but also an individual pursuit of active aging.